Acute blood transfusion reaction in a tertiary care hospital in Southern Punjab, Pakistan - Akhter, Naseem; Samad, Afra; Fayyaz, Nudrat; Habiba, Umme; Asif, Maliha; Fatima, Sabeen (International Journal Of Community Medicine And Public Health, 2019)
Background: Blood transfusion is a lifesaving process but carries many risks. Majority of these had been reduced with better diagnostic and management strategies. But the risk of non-infectious adverse transfusion reactions though reduced but cannot be eliminated. Hemovigilance is the system to monitor such reactions. Methods: The objective of current study was to know the frequency of adverse transfusion reactions and to compare it with local and international data. Retrospective cross-sectional descriptive study was done in Ibn-e- Sina hospital. Adverse transfusion reactions reported to blood bank was analysed according to hospital protocol. Results: Out of 6050 blood transfusions 23 (0.38%) develop adverse transfusion reactions. Febrile nonhemolytic transfusion reaction was the commonest adverse event and whole blood was the component implicated. Conclusions: Adverse transfusion reactions are non-infectious complications of blood transfusion which in spite of all efforts cannot be avoided. Frequency of adverse transfusion reactions in our study was 0.38% and Febrile nonhemolytic transfusion reaction was commonest reported reaction type. Hemovigilance system is necessary to monitor, investigate and control such activities.